2017
DOI: 10.9734/cjast/2017/34118
|View full text |Cite
|
Sign up to set email alerts
|

Response of Different Rice Varieties and Fertility Levels on Relative Economics and Quality of Rice under Aerobic Conditions

Abstract: The study was undertaken at Research Farm of Division of Agronomy, SKUAST-J, Chatha. The experiment was laid out in factorial randomized complete block design with four varieties viz.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
(5 reference statements)
2
0
0
Order By: Relevance
“…Baktash et al (2021) observed highest grain yield with the application of fertilizer with Azolla. The results are in conformity with earlier researchers (Kumar et al 2017, Razavipour et al 2018, Grace et al 2018. Significant variation was also observed amongst varieties in term of grain yield with hybrid 'AZ 6508' producing significantly higher grain yield followed by Vivekdhan 65, HPR 2720 and HPR 2143, in that order, each variety differing significantly from one another.…”
Section: Resultssupporting
confidence: 93%
“…Baktash et al (2021) observed highest grain yield with the application of fertilizer with Azolla. The results are in conformity with earlier researchers (Kumar et al 2017, Razavipour et al 2018, Grace et al 2018. Significant variation was also observed amongst varieties in term of grain yield with hybrid 'AZ 6508' producing significantly higher grain yield followed by Vivekdhan 65, HPR 2720 and HPR 2143, in that order, each variety differing significantly from one another.…”
Section: Resultssupporting
confidence: 93%
“…2). The significant and higher grain yield was recorded with the variety (BPT5204) might be due to greater vegetative growth and better light interception and higher dry matter portioning towards economic part, yield variability among rice cultivars also attributed to genetic characters and environmental effects .Similar results were reported by Kumar et al [25].…”
Section: Number Of Grains/paniclesupporting
confidence: 82%